Transubstantiation: Rethinking by Anglicans? - Douglas, Brian (New blackfriars, 2012)
This article examines the ways in which Anglican theologians have reflected on the doctrine of transubstantiation. The article notes that there is substantial agreement between the Roman Catholic Church and the Anglican Communion on the nature of Christ's presence in the Eucharist and that this agreement has been forged by the long established and continuing dialogue of the Anglican Roman Catholic International Commission (ARCIC). At the same time the article notes that official responses from the Roman Catholic Church, while acknowledging the worth of the dialogue, have insisted on particular theological and philosophical definitions of the nature of Christ's presence in the Eucharist concerning a change in the substance of the elements. While Anglicans have not accepted this particular definition of the real presence of Christ in the Eucharist as defined by the traditional doctrine of transubstantiation, they have nonetheless accepted the notion of the real presence and reflected in modern times on transubstantiation. Examples of this reflection on transubstantiation by Anglicans are discussed in the hope of allowing the dialogue to continue at new levels of understanding.